Case report: Genetic defects in laminin α5 cause infantile steroid-resistant nephrotic syndrome - Sunwoo, Yoon; Choi, Naye; Min, Jeesu; Kim, Jihyun; Ahn, Yo Han; Kang, Hee Gyung (Frontiers in Pediatrics, 2023)
Single gene pathogenic mutations have been implicated in up to 30% of pediatric steroid-resistant nephrotic syndrome (SRNS) cases, mostly in infantile patients. Among them is LAMA5, which has been recently discovered and encodes the laminin α5 chain. The laminin α5β2γ1 heterotrimer is an essential component of the glomerular basement membrane and is necessary for embryogenesis and immune modulation. Biallelic LAMA5 variants have been identified in one adult and ten pediatric nephrotic syndromes (NS) patients with variable phenotypes. Biallelic truncating mutations in this gene have recently been proven to cause SRNS. Here, we present another case of infantile SRNS related to novel compound heterozygous variations of LAMA5 (c.3434G > A, p.Cys1145Tyr and c.6883C > T, p.Gln2295*), the first reported case with one missense and one nonsense allele. A 10-month-old female patient presented with eyelid edema and massive proteinuria without any extrarenal symptoms or family history. The patient was diagnosed with SRNS. Renal biopsy revealed focal segmental glomerulosclerosis with widely effaced epithelial foot processes and a “moth-eaten” appearance. She progressed to end stage kidney disease (ESKD), requiring dialysis at 31 months of age, and underwent a deceased-donor kidney transplant at 6 years of age. Four months after transplantation, she developed Ebstein-Barr Virus (EBV) infection related to post-transplantation lymphoproliferative disorder (PTLD). After chemotherapy, the patient remained healthy with adequate renal function without disease recurrence for the past 7 years. We also identified previous cases of biallelic LAMA5 variants associated with the nephrotic phenotype and analyzed the available clinical and genetic information. All reported patients had an onset of NS ranging from 3 months to 8 years, with no other syndromic features. Response to therapy and renal outcomes varied greatly; most patients exhibited steroid resistance, five progressed to ESKD, and two received kidney transplantation (KT). There was one report of PTLD. Our patient’s phenotype was markedly more severe than those with biallelic missense variants and somewhat less severe than those with two truncating variants. LAMA5 defects may also play a role in PTLD, though no conclusions can be made with such limited cases. LAMA5 should be considered a candidate gene for SRNS and should be actively tested in cases with no other genetic diagnosis.